Sterilization efficacy of a warm-air circulation system in a vaporized hydrogen peroxide sterilizer - Mi Suk Noh; Su Yeon Lee; Eun Gyu Lee; Jonghyun Shin; Sang-Il Lee; Bong-Hyun Jun (PLoS ONE, 2026)
Background Vaporized hydrogen peroxide (VH 2 O 2 ) sterilization is a widely recognized method for low-temperature sterilization of medical devices. To overcome limitations associated with residual moisture and maximize sterilization efficacy, the integration of a warm-air circulation system (WACS) is proposed as a robust solution. Objective This study aimed to evaluate the effects of the WACS by comparing temperature uniformity and moisture removal with and without its operation. Additionally, the study assessed whether the WACS contributes to effective sterilization under conditions involving complex medical devices. Methods Temperature variations within the sterilization chamber and medical devices were monitored using sensors. The impact of the WACS on sterilization efficacy was assessed by introducing artificial moisture to the loading packages in cycles performed with and without the system. Sterilization efficacy was assessed through tests with various items, including process challenge devices (PCDs), flexible and rigid lumens, and dual flexible endoscope dummies. Results The WACS maintained a stable temperature of approximately 55 ~ 60 °C and effectively removed moisture throughout sterilization cycles, ensuring successful sterilization of all items. Conclusion This study demonstrates that the WACS significantly improves sterilization effectiveness by ensuring uniform temperature and effective moisture removal. This additional system in the VH 2 O 2 sterilizers will enhance the safety and sterilization efficacy of complex medical devices in healthcare settings.